Impacts of traffic noise in residential area of Permatang Pauh, Pulau Pinang - Hamzah, Nurakmal; Mohd Salehudin, Muhammad Syarafuddin; Abu Bakar, Amalina Amirah; Musir, Adhilla Ainun; Akbar, Nor Azliza (Universiti Teknologi MARA (UiTM), 2024)
Traffic noise has become an alarming issue in this era of urbanization where transportation and road traffic are the major sources of noise pollution in the environment. Frequent, intensifying noise pollution has become a potential health hazard to the community, causing sleep disturbances, noise-induced hearing loss and mental health problems. The aim of this study is to determine the current state of traffic noise levels at residential college located in Permatang Pauh, Pulau Pinang and to examine the perceptions of noise pollution in relation to health hazards among college students. Traffic noise levels were measured during peak hours and evaluated based on the permissible noise level by the DOE Malaysia. A questionnaire was distributed to assess the impacts of frequent noise exposure of traffic noise on the neighbouring residents. The on-site measurements show that the traffic noise levels more than 60 dBA, and the maximum recorded noise level is 86 dBA which exceeds the permissible limits specified by DOE Malaysia. The students agreed that the constant traffic noise presents health risks including headache (67.5%), sleep disturbances (69.8%) and nuisances to hearing system (53.5%). 79.1% of the respondents concurred that noise emitted by vehicle exhausts is the primary contributor to noise pollution. Hence, the findings of this study emphasize the relevance of setting rules for traffic noise levels and measures in reducing the health hazards of urban residents